Empowerment of Cocoa Farmers through Biotransformation Technology of Cocoa Pod Waste Integrated with BSF Maggot in Tettikenrarae Village, Soppeng Regency - Andi Besse Poleuleng (MALLOMO: Journal of Community Service, 2025)
Cocoa pod available in large quantity but utilization at the farmer still very limited. This condition creates potential environmental pollution and lost economic opportunities for farming communities. This activity aims to introduce and implement cocoa husk waste bio-transformation technology using Black Soldier Fly (BSF) maggots as an environmentally friendly innovation for producing animal feed. The activity was implemented through the Community Service in Tettikenrarae Village, Marioriwawo District, Soppeng Regency, with partners from the Sekkang Mata II Farmers Group. The implementation method included program socialization, training on BSF maggot cultivation, cocoa pod processing practices, and mentoring in the application of bio-transformation technology in the field. The results of the activity showed an increase knowledge and skills in utilizing agricultural waste into value-added products. The resulting bio-transformation product is animal feed with high protein content that can be reused on agricultural land. In addition, this activity raised public awareness of the importance of sustainable waste management and opened up new economic opportunities based on environmental biotechnology. Thus, the application of BSF maggot technology has proven effective as an innovative solution in managing agricultural waste and improving the welfare of cocoa farmers in a sustainable manner.